The Energy Structure of Kazakhstan and Its Environmental Impact - AMIRBEKOVA, Ainur B.; UKUBASSOVA, Galiya S.; GALIYEVA, Alma; YELSHIBAYEV, Rakymzhan K.; KOZHABAEVA, Saule A. (Journal of Environmental Management and Tourism, 2020)
One of the main factors in the development of mankind and a necessary means of subsistence is energy production, but there is also a downside – environmental impact. Energy has become a part of a human’s life, production activity, however, the environmental aspect of energy use is becoming no less significant, considering the intensity of the impact. Mankind is actively seeking cleaner energy production and more efficient technologies within its use, which are more economical. It can be noted that the current stage of development is based on the “three pillars”: Energy, Ecology, Economics. A special place is given to the energy sector, since this is the main factor that determines both the environment and the economy. Regarding the economy in this situation, it is possible to talk about the well-being of people and the economic potential of the country. As for ecology, in this direction the negative impact of energy, direct or indirect (production and use) is significant. Here it is about the biosphere as a whole and about the ecosystem. In this context, it is about thermal, radioactive, chemical, aerosol and many other types of pollution. The energy problem is quite acute, the solution of this problem depends on the resolution of both economic and environmental problems. The aim of the article is to analyse the structure of the energy sector in Kazakhstan and determine its impact on the environment with consideration of directions to reduce the negative impact. As part of the study, the role of energy for the state, as well as for ecology, is determined, the modern aspects of energy development in the world are considered, the issue of combating emissions at the international level is also covered, the main international agreements are described to limit the negative impact of energy on the environment. The structure of Kazakhstan’s energy, energy production and emissions are considered. The data were studied in comparison with other countries (USA, China, Germany, Russia), the main problems were identified, and prospects for the development of renewable energy were also considered. The prospects for further research are determined by the subsequent study of the development of energy and its impact on the environment and the prospects for the development of alternative energy. The article is of practical value within data generalisation on the development of energy in Kazakhstan and foreign countries.